LONELINES: BETWEEN DILEMMA AND RENUNCIATION - Angelika Amanda Octaviana; Santia Oktaviani, Paulina Gresia, Linta, Lien Meilan, Yumi, Yola Pradita, Yesyurun Munthe (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
This paper examines the impact of lack of social support on the experience of solitude or loneliness in adolescents at the high school (SMA) level. This research involved surveys and interviews with a number of high school students to analyze the factors that influence their level of loneliness. Findings highlight the close relationship between insufficient social support and increased risk of loneliness in adolescents. The psychosocial implications of this phenomenon are also explored, providing in-depth insight into the important role of social support in supporting high school students' emotional well-being.